Effects of Anatomy and Particle Size on Nasal Sprays and Nebulizers - Frank, Dennis O. (2011)
OBJECTIVE: To study the effects of nasal deformity on aerosol penetration past the nasal valve (NV) for varying particle sizes using sprays or nebulizers. STUDY DESIGN: Computed mathematical nasal airway model. SETTING: Department computer lab SUBJECTS AND METHODS: Particle deposition was analyzed using a computational fluid dynamics model of the human nose with leftward septal deviation and compensatory right inferior turbinate hypertrophy. Sprays were simulated for 10µm, 20µm, 50µm, or particle sizes following a Rosin Rammler Particle Size Distribution (10–110µm), at speeds of 1m/s, 3m/s, or 10m/s. Nebulization was simulated for 1µm, 3.2µm, 6.42µm, or 10µm particles. Steady state inspiratory airflow was simulated at 15.7L/min. RESULTS: Sprays predicted higher NV penetration on the right side for particle sizes >10µm, with comparable penetration on both sides at 10µm. Nearly 100% deposited in the nasal passages for all spray characteristics. Nebulizer predictions showed nearly 100% of particles <6.42µm and over 50% of 6.42µm bypassing both sides of the nose without depositing. Of the nebulized particles that deposited, penetration was higher on the right at 10µm, with comparable penetration on both sides at 6.42µm. Spray penetration was highest at 10µm, with over 96% penetrating on both sides at 1 and 3m/s. Nebulization penetration was also highest at 10µm (40% on the left, >90% on the right). CONCLUSION: In the presence of a septal deviation, sprays or nebulizers containing 10µm particles may have good penetration beyond the NV. Nebulized particles <10µm are likely to be respirable. Additionally, spray speeds above 3m/s may limit penetration.